The impact of irrigation procedures on the bond strength of fiber posts cemented with two different adhesive techniques - Apostolska Sonja; Andonovska Marija; Rendžova Vasilka (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction Endodontically treated teeth are usually weaker due to the loss of tooth structure. As most of the crown of the tooth is destroyed, the most common retention for restoration is application of a fiber-reinforced composite posts in the root canal. In endodontically treated teeth, there are two main problems in the restorative procedure: reduced resistance of the remaining tooth structure and choosing the necessary adequate retention for restoration. The aim of this work was to evaluate the impact of irrigation protocol on the bond strength of two types of fiber posts luted with two different adhesive cements. Materials and method In this in vitro study, 48 single-rooted teeth (incisors, single-rooted second premolars) extracted for orthodontic and periodontal reasons were used. The teeth were divided into the four groups of 12 teeth depending on the type of fiber post used as well as the irrigation agent. Each group was further divided into the two subgroups of six teeth depending on the material and cementation technique. Results In all cross-sectional statistics the difference appeared only when different types of irrigants were used and they changed bond strength between dentin and bonding material. Conclusions Irrigation protocol has a significant influence on the bond strength of composite post, independent of the type of post and cementation material used.